Students’ Perceptions on Using Vlog to Improve English Speaking Skills - Istiqamah, Alisya Fitria; Jefri, Riny; Hajar, Andi (Journal of Excellence in English Language Education, 2025)
This study investigates the perceptions faced by Business English Communication (BEC) students at Universitas Negeri Makassar on using video blog (Vlog) to improve their English-speaking skills. Using a qualitative research approach, this study aims to describe students' views on the efficacy of Vlog as a learning tool and to identify the barriers they face in this process. Data was collected through interviews with students who extensively use Vlog outside of course requirements. The findings show that students' perceptions regard Vlog as a useful medium for improving speaking skills due to their engaging and interactive nature. These insights contribute to the theoretical understanding of media-based learning and offer practical implications for educators and curriculum developers who aim to integrate digital media effectively into language learning programs.